Description of the male, nest architecture and biology notes of Zethus plaumanni Bohart amp; Stange, 1965 (Hymenoptera, Vespidae) in southern Brazil - Lopes, Rogrio B. [UNESP]; Brozoski, Franciele; Buschini, Maria Luisa T (Magnolia Press, 2021)
Although diverse and widespread, there is much to improve on the knowledge of Zethus Fabricius, 1804 wasps. This includes aspects of many areas, such as data on taxonomy, behavior and biology. In the present study, we investigated Zethus plaumanni Bohart Stange, 1965, a species hitherto known only from the female type in the literature, and worked to fill gaps on the knowledge of this species by describing the male and its genitalia, the nest structure and giving notes on the biology of individuals collected in trap-nests in southern Brazil. The male is diagnosable by characters also used for female identification. The nest follows the pattern of typical pre-existing cavity users, with a remarkable multi-layered nest plug. Sex ratio follows the 1:1 rule and sampling indicates diapause in the adult phase.